2011
DOI: 10.1371/journal.pcbi.1002134
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Accessibility of Mutational Pathways

Abstract: Functional effects of different mutations are known to combine to the total effect in highly nontrivial ways. For the trait under evolutionary selection (‘fitness’), measured values over all possible combinations of a set of mutations yield a fitness landscape that determines which mutational states can be reached from a given initial genotype. Understanding the accessibility properties of fitness landscapes is conceptually important in answering questions about the predictability and repeatability of evolutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
375
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 204 publications
(385 citation statements)
references
References 50 publications
(89 reference statements)
9
375
1
Order By: Relevance
“…Several reports have documented both inter- [4,5,56] and intralocus [27,57,58] sign epistasis in different model systems. These observations promoted the idea that genetic constraints could be prevalent and hence adaptation could proceed through very few mutational paths to optimal genotypes [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented both inter- [4,5,56] and intralocus [27,57,58] sign epistasis in different model systems. These observations promoted the idea that genetic constraints could be prevalent and hence adaptation could proceed through very few mutational paths to optimal genotypes [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Although some models have recognized the importance of deleterious intermediates and the crossing of fitness valleys to the overall adaptive evolution of pathogens (27,29,42,43) and the possibility that multiple simultaneous mutations can overcome such fitness valleys (44), various other models assume a strong selection-weak mutation paradigm (32)(33)(34)45), ignoring any adaptive trajectories that require the crossing of a fitness valley. Such assumptions might be appropriate for small population sizes or pathogens with low mutation rates (5,30).…”
Section: Discussionmentioning
confidence: 99%
“…A methodological framework that is frequently used to study pathogen evolution and that makes such assumptions is the strong selection-weak mutation (SSWM) approximation (30,31). Models using the SSWM assumption describe the evolutionary trajectory of a population where selective sweeps cause the sequential fixation of advantageous mutations, while deleterious or neutral mutations are disregarded (32)(33)(34).…”
mentioning
confidence: 99%
“…As a consequence, a mutational pathway connecting two genotypes is selectively accessible in the SSWM regime only if fitness increases in each step (22). A number of recent studies of empirical fitness landscapes have shown that, in most cases, only a small fraction of possible adaptive pathways are accessible in this sense, which implies a dramatic enhancement of evolutionary predictability (10,11,15,(23)(24)(25)(26)(27). Moreover, the statistical weights of different accessible trajectories often vary widely, further narrowing the range of possibilities to a small number of dominant evolutionary pathways (10,11,15).…”
mentioning
confidence: 99%